(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2021)
Libraries are undergoing major changes because of the increasing use of digital tools and resources. But they still need to maintain their physical collection, which requires modernization of their activities, as in the case of the cataloging process. However, most libraries adopt integrated library systems, which requires studies to verify the effectiveness of these systems to new standards such as the Resource Description Access (RDA) and the Library Reference Model (LRM). Thus, this study aims to verify the suitability of the Koha software for the use of RDA and LRM in the cataloging process, since Koha software is a free open source tool most used in the world for computerization of libraries, especially in the management of physical collections. The study has exploratory characteristics, due to the little familiarity in Brazil with the theme, with qualitative alignment. The results showed that the adoption of RDA and LRM in Koha is possible and technologically easy to implement. However, the biggest challenge is in technical issues, since the RDA and LRM involve conceptual models appropriate to technological changes. Thus, the present study verified the need for further studies aimed at verifying the use of RDA and LRM in other activities of the library, presenting an opportunity for new researches. Keywords: RDA. LRM. Cataloguing. Open software. Link: https://periodicos.ufpb.br/ojs2/index.php/ies/article/view/54063/31481